American Trypanomiasis and Chagas Disease Sexual Transmission to Naïve Mates: Prevention And Control - Teixeira, Antonio R. L. (Advances in Social Sciences Research Journal, 2024)
Chagas disease is the most lethal endemic condition in the Western Hemisphere. Its high morbidity and mortality make the disease a major public health problem in Latin America. At the public hospitals’ autopsy rooms, Chagas cardiomyopathy is a leading cause of people’s death, usually at 45 ± 10 years of age. Over the last decades, the disease epidemiologic profiles changed drastically with migration to the five Continents. The immigration of people from Latin America to the Northern Hemisphere bears health concerns, notably, the sexual transmission of Trypanosoma cruzi agent of Chagas disease from males and females to naïve mates, and its vertical transference to progeny. The family-based Chagas disease introduces substantial changes in concepts of disease prevention and control. The treatment of Chagas disease with nitro derivatives is unsatisfactory. In the absence of a drug to eradicate the T. cruzi infection, its control requires a robust program of education, information, and communication for health. Its prevention can be achieved through social activists participating in public and private organizations at schools, social clubs, churches, and people’s organizations for health and education.